Memories of shame experiences with others and depression symptoms: the mediating role of experiential avoidance - Carvalho, Sérgio (2015)
Background: Shame experiences have been suggested to be related with psychopathological symptoms and with self-relevant beliefs. Recent studies also suggest that avoidant-focused strategies (e.g., rumination, thought suppression and dissociation) mediate the impact of shame memories and depression symptoms. However, experiential avoidance has been found to mediate the relation between early experience of abuse and psychopathological symptoms. Our goal was to test the mediating effect of experiential avoidance in the relation between both the nature of shame experiences at the hands of caregivers and the centrality of shame memories with others, and depression symptoms. Method: Using structural equation modelling, we assessed the frequency and nature of recalled shame experiences at the hands of caregivers, the centrality of shame experiences with others throughout childhood and adolescence, experiential avoidance and depression symptomatology in 161 participants from general population. Results: Experiential avoidance mediates the impact of shame experiences with caregivers and depression symptoms. Experiential avoidance also mediated the association between the centrality of shame experiences with others and depression symptoms. Conclusion: Our results suggest that shame memories with others do not per se impact on depression symptoms, but rather the unwillingness to experience them and the attempts to control them. Hence, our results emphasize the importance of addressing affect regulation processes such as avoidance when dealing with shame memories, particularly with patients who experience depression symptoms.